Aesthetic Place in Kurdish Folkloric Songs ( Teli’s Song as a case study) - Othman, Salar; Omar, Payman (Humanities Journal of University of Zakho, 2022)
This research, it is entitled(Aesthetic Place in Kurdish Folkloric Songs( Teli’s Song as a case study), it is an attempt to illustrate the role and station of place. Human beings have no existence on this earth without a place. The places that human beings are living on are not the only geographical place, but it carries the experiences, value, and the meaning of Humanity, which means, the place has an impact on the psychology, indicating the personal identity, and characteristics of the humans. So, whichever type of the personality, that means, place has an authority and it becomes a reason behind having different class people in the society. Undoubtedly, humans have also a great impact on the place, thus, it relates to the human thinking progress. Means that, the relationship between the place and human beings is a multi-face, influential, and meaningful. Place, based on its types, has its position in the literary text and it will be meaningless without the existence of that place. In this paper, the statisttical descriptive analysis reading has been done to “Aesthetic Place in Kurdish Folkloric Songs( Teli’s Song as a case study) “Teli’s Song, is a folkloric song from Northern Kurdish. It deals with the love and admiration through the glorification and description of Teli’s lady and her Lover. It utters from the depth of the place. Which means, throughout an attractive literary description to Tel’s song, the aesthetic place is embodied, as a literary board that several various pure places are embodied. This study is a scientific land-living argument about the place in the Kurdish folkloric text. It aims to introduce and going deeply through the folkloric texts of Kurdish nation. By addressing the value of the place and identifying the ratio of the its types usage in that Kurdish folkloric song.